1908
DOI: 10.1021/ja01947a015
|View full text |Cite
|
Sign up to set email alerts
|

THE EXTRACTION OF POTASH FROM FELDSPATHIC ROCK.1

Abstract: The extraction of potash from native rocks has long been considered one of the most important as well as one of. the most difficult problems of industrial chemistry. In spite of the enormous resources of the .North American continent, there has not yet been found anywhere on it an available source of potash, thus necessitating the importation from abroad of many hundreds of millions of pounds per annum of the salts and compounds of this important substance. One result of this lack of a native source of supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1912
1912
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The former mainly centered on the use of hydrofluoric acid (HF). The latter centered on attempts to liberate potassium via formation of amorphous and/or new solid-state phases (Cushman and Coggeshall, 1912;Cushman and Hubbard, 1908;Ross, 1913;Ross, 1917;Spiller, 1882). This second approach was probably the logical consequence of applying treatments similar to the analytical method of Lawrence Smith (Hart, 1915;Smith, 1871).…”
Section: Production Of Potash From Silicate Mineralsmentioning
confidence: 99%
“…The former mainly centered on the use of hydrofluoric acid (HF). The latter centered on attempts to liberate potassium via formation of amorphous and/or new solid-state phases (Cushman and Coggeshall, 1912;Cushman and Hubbard, 1908;Ross, 1913;Ross, 1917;Spiller, 1882). This second approach was probably the logical consequence of applying treatments similar to the analytical method of Lawrence Smith (Hart, 1915;Smith, 1871).…”
Section: Production Of Potash From Silicate Mineralsmentioning
confidence: 99%
“…Publications dealing with the acidic dissolution of silicate rocks date back to the early 20th century (Cushman and Hubbard, 1908). Varadachari (1992) showed that potassium can be recovered from biotite through concentrated acidic solutions.…”
Section: Introductionmentioning
confidence: 99%